An update on hepatitis C virus. - Klenerman, P; Fitzmaurice, K (Royal College of Physicians, 2015)
Chronic hepatitis caused by hepatitis C virus infection is one of the leading causes of liver cirrhosis and hepatocellular carcinoma globally. Over the last few years, there have been significant advances in our understanding of the immunopathogenesis of this infection, as well as revolutionary developments in the therapeutic armamentarium. The introduction of a number of new oral antiviral agents is already delivering major benefits to patients as they are generally well tolerated and are associated with excellent response rates in the majority. Nonetheless, a number of clinical scenarios remain challenging and research is ongoing in these areas. In this update, we review developments in both basic as well as translational research in the field.